Good correlation between visual analogue scale and numerical rating scale in the assessment of nasal obstruction. Issue 4 (15th February 2018) - Haye, R; Døsen, L K; Tarangen, M; Shiryaeva, O
Abstract: Objective: Results from telephone interviews may be needed to supplement those from mailed questionnaires when response rates are inadequate. This study assessed the correlation between visual analogue scale ratings used in mailed questionnaires and numerical rating scale scores used in telephone interviews. Methods: Patients scheduled for nasal septal surgery routinely respond to a visual analogue scale of obstruction during the day and at night. In this study, they were also asked to verbally rate their sense of obstruction using whole numbers. Results: There was no significant difference between visual analogue scale and numerical rating scale obstruction scores. Conclusion: Ratings of nasal obstruction obtained with a numerical rating scale in telephone interviews are comparable to visual analogue scale scores in mailed questionnaires.